ANALISIS MOTIVASI BELAJAR SISWA (Studi Tentang Peserta Didik yang Memiliki Motivasi Rendah Di SekolahMenengah Atas Santun Untan Pontianak) - Ismi Tri Wahyu Yuha; Indri Astuti; Ana Fergina (Universitas Tanjungpura, 2021)
AbstractThis study aims to analyze students' learning motivation (study of students who have low motivation at Santun Untan Pontianak High School). The research method used is descriptive with a qualitative research approach. The data sources of this research are homeroom teachers, subject teachers, counseling guidance teachers, and students whose learning outcomes are below the minimum completeness criteria. Interview data collection techniques. Data analysis using an interactive model consists of data reduction, data presentation and conclusion drawing. The results of the study show that the factors that influence low learning motivation are the ability of teachers, students' abilities, and the condition of parents of students, the impact of low learning motivation is not being able to carry out tasks, quickly despairing, indifferent to their own problems, depending on other people, and cannot be responsible for the tasks given, and the efforts of Guidance and Counseling teachers to increase low learning motivation, namely adjustments to the implementation of learning needed by students, such as when starting learning the teacher can start with questions, During the learning process the teacher stimulates In order to create the attractiveness of the lesson, it can be done by holding games. At the end of learning the teacher must evaluate and provide input. Teachers must provide grades, give rewards or prizes, build competitive competitions, and notify learning outcomes.Kata Kunci: Motivasi Belajar Rendah